"To Choose Freely and Responsibility": Race, The Family and the "Right to Choose" in Birth Control Programmes Before Roe vs. Wade. - Russell, Clare (2006)
The dissertation argues that although in contemporary America, the concept of women having an individual and constitutional "right to choose" is central to the abortion rights and pro birth control movement; before the 1973 Roe versus Wade decision, birth control was advocated less as a woman's individual right. Instead, the legalisation and promotion of birth control methods and programmes was justified in terms of its benefits for society and for establishing stable family structures. Furthermore, discourse on the birth control promotion could not escape prevalent racial issues. In the 1920s, Margaret Sanger argued that small family size would ensure healthy, happy children who were essential for the development of the American race, while in the 1960s social scientists and policymakers like Daniel Patrick Moynihan argued that birth control could ensure that black families conformed to the white middle class norms. However, although "choice" was far from the central rationale behind birth control promotion, case studies of birth control programmes indicate that not only were they voluntary, they also took steps to create "enabling conditions" which guaranteed women's rights to choose.